Fuzzy Methods in Marketing Research: Brief Literature Review - Dorokhova Liudmyla; Dorokhov Oleksandr; Kuusik Andres (Studies in Business and Economics)
Background: Literature studying is a critical step in research. It allows identified gaps, unresolved issues, research directions, methods, and models for use. Accordingly, publication review is an ongoing task. A lot of poorly defined data makes it difficult to use precise methods, and require new approaches for their processing. One of them is fuzzy modeling. Today it is used little in marketing, therefore there is a need to analyze examples and outline possible it’s applications in marketing. Objectives: The object of the review was to study publications describing fuzzy methods for marketing problems. The purpose was to systematize the fuzzy modeling methods for solving marketing problems. Methods: The publications were selected based on content analysis. Then, its’ bibliometric data were collected and analyzed, which can be methodologically useful for authors conducting similar studies. Results: The most used fuzzy methods for solving marketing problems were identified. The strengths, weaknesses, limitations, and prospects for using fuzzy approaches in connection with tasks of marketing were indicated. Conclusions: The results significantly complement the general understanding of the place and role of fuzzy methodology in marketing research, and provide practical information regarding the subsequent publication of their results.